(untitled) (Bangladesh Journal of Botany, 2018)
Raw peanut kernel samples were collected from 13 areas of Bangladesh for determination of mycoflora and mycotoxin. Fungi associated with the tested samples throughout the investigation were Aspergillus flavus, A. niger, Aspergillus sp. (1), Aspergillus sp. (2), Penicillium sp., Fusarium sp., Rhizopus sp. and Curvularia sp. A. flavus was the most common fungus followed by A. niger. Colonies of fungi were found to form 79.81 to 98.10% of raw peanut kernels. Out of the 13 samples, eight were found to be contaminated with 11.91 to 182.6 ppb of total aflatoxins and five samples were free from aflatoxins.